2015
DOI: 10.1002/ppul.23241
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial wall thickness in Eisenmenger Syndrome: Prospective, cross-sectional, controlled clinical trial

Abstract: PAWT can be used as an additional parameter with other echocardiographic parameters in the follow-up of Eisenmenger Syndrome in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…The remarkable study from Narin et al clearly supports the notion that the RV is highly susceptible to chronic pressure overload in pediatric patients with severe PH. This might emphasize the importance of their data for future follow‐up examinations in children with different forma of PH.…”
Section: To the Editormentioning
confidence: 80%
See 3 more Smart Citations
“…The remarkable study from Narin et al clearly supports the notion that the RV is highly susceptible to chronic pressure overload in pediatric patients with severe PH. This might emphasize the importance of their data for future follow‐up examinations in children with different forma of PH.…”
Section: To the Editormentioning
confidence: 80%
“…Recent studies on pediatric idiopathic PH, and in PH‐patients secondary to congenital heart disease (CHD) suggest that the systolic RV function progressively deteriorates over time . About half of the PH patients in childhood have an underlying CHD, which highlights the importance of noninvasive echocardiographic tools for the evaluation of the RV systolic function in these patients, as suggested by Narin et al Their findings in children with the Eisenmenger Syndrome add up to recent data in PH‐CHD patients showing increased RV wall thickness and impaired RV systolic function . Narin et al concluded that determination of the TAPSE is a promising technique to monitor RV function in children with severe PH.…”
Section: To the Editormentioning
confidence: 94%
See 2 more Smart Citations